2015
DOI: 10.3168/jds.2014-8871
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of concentrations of cortisol in hair with health, biomarkers in blood, and reproductive status in dairy cows

Abstract: Hair cortisol has been used to measure chronic stress in dairy cows as it offers the advantage of being noninvasive, fast, and able to indicate levels of cortisol over long periods. The aim of this study was to determine the associations between hair cortisol with clinical disorders, reproductive status, and the development of subclinical endometritis in dairy cows. Furthermore, we aimed to determine the association between hair cortisol concentrations and blood markers associated with metabolic status and acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 40 publications
5
70
1
1
Order By: Relevance
“…Chronically ill cows had higher hair cortisol concentrations than acutely ill cows, which was in agreement with findings of another study (Burnett et al, 2015). There was no correlation overall between hair cortisol concentration and adrenal gland weight.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Chronically ill cows had higher hair cortisol concentrations than acutely ill cows, which was in agreement with findings of another study (Burnett et al, 2015). There was no correlation overall between hair cortisol concentration and adrenal gland weight.…”
supporting
confidence: 82%
“…Hair cortisol concentration therefore has evolved as a novel biomarker for chronic stress in humans (Russel et al, 2012). There have been several studies on hair cortisol concentrations in healthy and ill cattle (González-de-la-Vara et al, 2011;Comin et al, 2011Comin et al, , 2012Comin et al, , 2013Peric et al, 2013;Burnett et al, 2014Burnett et al, , 2015; ill cattle have higher concentrations than healthy cattle Burnett et al, 2015). To the authors' knowledge, there have been no studies comparing adrenal gland weight and hair cortisol concentrations in cattle.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several authors have reported the correlation between altered physiologic status and high hair cortisol concentrations (Burnett et al, 2015, Comin et al, 2012a, Comin et al, 2012b, Comin et al, 2013, Corradini et al, 2013). Galuppi et al (2013) studied the relation between Microsporum canis infection in cats and hair cortisol concentrations, but so far no one has considered parasitic loads and hair steroids concentrations (Galuppi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale investigation in the United States revealed that deep-bedded and well-maintained stalls reduce the risk of hock injuries (Barrientos, Chapinal, Weary, Galo, & Keyserlingk, 2013). Although more investigations are necessary, Several studies have examined the effect of parturition on hair cortisol concentrations in dairy cows (Braun, Michel, Baumgartner, Hassig, & Binz, 2017;Burnett et al, 2014Burnett et al, , 2015Endo, Kuroki, & Tanaka, 2017). When hair was collected at three-week intervals from 0 to 126 days postpartum from healthy lactating cows, increased hair cortisol concentrations were only found during the early lactation period of 0-21 days postpartum (Burnett et al, 2014).…”
Section: Discussionmentioning
confidence: 99%